2020
DOI: 10.9734/ajee/2020/v12i130151
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Palm Oil Mill Effluent Pollution Impact on Groundwater Quality and Agricultural Soils

Abstract: A field study was conducted to investigate palm oil mill effluent (POME) pollution impact on ground water quality and agricultural soils. Raw POME and two water samples were also collected from the downstream and upstream locations away from the effluent discharge point using 1 litre capacity container. This was found less than 100 m from the mill. Soil samples from the POME dumpsite as well as non-POME soil were collected. Temperature, pH, electrical conductivity (EC), salinity, total hardness, turbidity, sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The POMEaffected soils gave a mean pH value of about 4.5 and are less acidic compared to those of the adjacent non-POME-affected ones with a mean of about 3.9. Maliki et al, (2020) reported similar increase in pH of POME-treated soils compared with that of untreated soils, and is in agreement with the findings of some of the other similar reports which indicated that raw POME, though acidic in reaction, gradually becomes alkaline with time as biodegradation by microbes sets in (Nta et al, 2020;Osubor and Oikeh, 2013;Nwoko and Ukiwe, 2016). The result, however, is in contrast with the findings of Awotoye, et al, (2011) and Chinyere, et al, (2018), both of which showed that the non-POME affected soils were more alkaline than the POME affected soils.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The POMEaffected soils gave a mean pH value of about 4.5 and are less acidic compared to those of the adjacent non-POME-affected ones with a mean of about 3.9. Maliki et al, (2020) reported similar increase in pH of POME-treated soils compared with that of untreated soils, and is in agreement with the findings of some of the other similar reports which indicated that raw POME, though acidic in reaction, gradually becomes alkaline with time as biodegradation by microbes sets in (Nta et al, 2020;Osubor and Oikeh, 2013;Nwoko and Ukiwe, 2016). The result, however, is in contrast with the findings of Awotoye, et al, (2011) and Chinyere, et al, (2018), both of which showed that the non-POME affected soils were more alkaline than the POME affected soils.…”
Section: Resultssupporting
confidence: 89%
“…Osunbor and Oikeh (2013), who reported similar increased conductivity of POME-treated soils, compared to non-POME affected soils. Nta, et al, (2020) also reported highly significantly different values of electrical conductivities between POMEand non-POME soils of Abak Local Government area, AkwaIbom state, Nigeria. Mean values of available phosphorus were respectively, 5.31 and 3.08 mg/dm 3 in POME and non-POME soils, with no significant difference (P<0.05).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…For the Palm Tree planter, it would reduce fertilizer cost significantly while at the same time decrease the volume of wastewater in the Wastewater Treatment Plant. Nevertheless, a land application could potentially harm the environment and causing pollution to groundwater, soil [11], and tributaries especially if the land application site is not suitable; causing POME to disperse uncontrollably. The impact could be more severe depending on the physical characteristic.…”
Section: Introductionmentioning
confidence: 99%